Radiotherapy with rituximab may be better than radiotherapy alone in first-line treatment of early-stage follicular lymphoma: is it time to change the standard strategy?. Issue 8 (3rd August 2015) - Janikova, Andrea; Bortlicek, Zbynek; Campr, Vit; Kopalova, Natasa; Benesova, Katerina; Belada, David; Prochazka, Vit; Pytlik, Robert; Vokurka, Samuel; Pirnos, Jan; Duras, Juraj; Mocikova, Heidi; et al.
Abstract : Early-stage follicular lymphoma (FL) has traditionally been treated with involved-field radiotherapy (RT). Rituximab (R) is a low-toxic, efficient systemic therapy for FL, but there are no data about its clinical impact in early FL. We retrospectively analyzed 93 patients with stage I–II indolent FL treated with RT ( n = 65) or RT + R ( n = 14) or R alone ( n = 14). Median follow-up was 5.0 years for patients with RT, 2.8 years for the RT + R subgroup and 2.5 years for patients treated with R. The complete response rate was 92%, 100% and 86% (not significant) and the median PFS was 3.3 years, not reached and 4.9 years ( p = 0.035) for the RT, RT + R and R arms, with no impact on overall survival. R combined with RT seems to give better results in terms of global FL control, but longer follow-up and prospective comparison are needed to verify these results.